Peningkatan Pengetahuan dan Kesadaran Siswa SD Negeri Kretek 1 Mengenai Pola Hidup Sehat, Gizi Seimbang, dan Bahaya Malnutrisi - Agung Nugroho Puspito; Mohammad Ubaidillah; Najwa Gia Verizkyani; Ladynda Dewilova Memmase; Alza Annisa Nidaan Khofia; Abd.Rokhman Muhammad; Shela Nur Kamalin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Nutrition plays an important role in supporting the growth, development, and learning abilities of elementary school children. Elementary school students are an age group that is still vulnerable to nutritional status, this is due to the rapid growth and development of children and a relatively busy school schedule. The method of this activity is in the form of counseling and implementation of Healthy Lifestyle and Balanced Nutrition for elementary school students, precisely at Kretek 1 Elementary School located in Kretek Village, Taman Krocok District, Bondowoso Regency. The purpose of this social project is to provide education to improve students' knowledge and behavior regarding healthy lifestyles and the implementation of nutritious food consumption so that it becomes a habit in everyday life. By implementing this healthy lifestyle, students can avoid malnutrition problems and have a better quality of life in the future.